Comparison of quantitative regional perfusion‐weighted phase resolved functional lung (PREFUL) MRI with dynamic gadolinium‐enhanced regional pulmonary perfusion MRI in COPD patients. Issue 4 (22nd October 2018) - Kaireit, Till F.; Voskrebenzev, Andreas; Gutberlet, Marcel; Freise, Julia; Jobst, Bertram; Kauczor, Hans‐Ulrich; Welte, Tobias; Wacker, Frank; Vogel‐Claussen, Jens
Abstract : Background: Perfusion‐weighted noncontrast‐enhanced proton lung MRI during free breathing is maturing as a novel technique for assessment of regional lung perfusion, but has not yet been validated in chronic obstructive pulmonary disease (COPD) patients. Purpose: To compare pulmonary parenchymal perfusion assessed by noncontrast‐enhanced perfusion‐weighted phase‐resolved functional lung (PREFUL)‐MRI with lung perfusion determined with dynamic gadolinium‐enhanced (DCE)‐MRI and with lung function test parameters. Study Type: Prospective. Population: A single‐center subset of the COPD cohort "COPD and SYstemic consequenzes‐COmorbidities NETwork" (COSYCONET). Forty‐seven patients with COPD (median age 66 [57–70] years) were studied. Field Strength/Sequence: For PREFUL‐MRI a spoiled gradient echo sequence and for DCE‐MRI, a 3D time‐resolved spoiled gradient echo sequence was used at 1.5T. Assessment: PREFUL‐MRI coronal slices were acquired in free breathing. DCE‐MRI was performed in breath‐hold with administration of 0.025 mmol/kg bodyweight of gadobutrol i.v. at a rate of 4 ml/s and pulmonary blood flow (PBF) maps were calculated. Slices of PREFUL and DCE‐MRI were matched by their ventrodorsal position and corresponding slices were coregistered for evaluation. Perfusion defect percentages (QDP) were calculated for both methods. Statistical Tests: The obtained parameters were correlated using Spearman's correlation coefficient ( r ) and Bland–Altman plot analysis. Results: PREFUL‐QDP showed an absolute and spatial agreement with PBF‐QDP on a global (39.3 (31.8–45.5)% vs. 44.7 (35.4–50.0)% with a spatial overlap of 62.2 (57.2–67.2)%)) as well as on a lobar level and correlated with lung function test parameters (PREFUL‐QDP vs. FEV1, r  = –0.75, P < 0.0001). There was a systematic overestimation of PREFUL‐QDP compared with PBF‐QDP, mainly in the lower lobes, resulting in an overall overestimation for the whole lung with a mean difference of 5% (95% confidence interval [CI]: 3.0%; 7.0%; STD 6.8%). Data Conclusion: PREFUL‐MRI is a promising noninvasive, radiation‐free tool for quantification of regional perfusion in COPD patients. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:1122–1132.